The Effectiveness of Three-Sided Splinting on he Degree of Pain in Patients with Closed Fractures of the Lower Extremities in the Emergency Room - Geu, Yafet; Mardiyono, Mardiyono; Sudirman, Sudirman; Walin, Walin (Indonesian Journal of Global Health Research, 2024)
Trauma from accidents that cause fractures can lead to complications including epistaxis, internal organ injury, injury inflammation and respiratory syndrome. The occurrence of a fracture causes destruction of nerves and blood vessels which causes pain. Pain then increases in severity until the bone is immobilized. Pain in a fracture is not caused by the fracture itself, but by the injury to the tissue around the broken bone and the movement of the bone fragments. Correct dressing of the fracture can reduce pain in patients, especially for closed fractures. Three-sided splinting is one option to minimize movement in long bones because it is felt to be stronger to withstand movement because the broken bone is flanked from three opposite sides of the broken bone. Objective: To determine the effectiveness of three-sided splinting on the degree of pain in patients with closed fractures of the lower extremities. Methods: The research design used quasy experimental with pre-test and post-test control group design. The research sample was 30 respondents, the sample selection method used purposive sampling which was divided into control and intervention groups. The control group used two-sided splinting while the intervention group used three-sided splinting. Data analysis used demographic characteristics and research variables, namely three-sided splinting and pain levels. Bivariate analysis used Wilcoxon and Mean Withney. Results: Both groups of respondents experienced a decrease in pain levels after treatment but the decrease in pain levels was greater in the intervention group using three-sided splinting. The results showed that the three-sided splinting action was very effective in reducing the degree of pain with p=0.000. Conclusion: Three-sided splinting is proven to be more effective in reducing the degree of pain in patients with closed fractures of the lower extremities.